Lithium sulfide / carbon composite material and preparation method and application thereof

The polystyrene ball template pyrolysis formed a graded porous carbon structure and uniformly loaded lithium sulfide thereon, which solved the problem of uneven composite of lithium sulfide and carbon materials in the prior art, and achieved a lithium sulfide/carbon composite with high conductivity and electrochemical properties.

CN119812448APending Publication Date: 2025-04-11JIAOZUO BANLV NANOMATERIALS ENG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411824651.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, when preparing lithium sulfide/carbon composite materials, it is difficult to achieve uniform composite between lithium sulfide and carbon materials, resulting in low utilization rate of lithium sulfide and poor electrochemical performance.

Method used

Through the synthesis and pyrolysis of polystyrene ball templates, a graded porous carbon structure is formed, and lithium sulfide is uniformly loaded thereon, and a zeolite imidazole ester skeleton structure is formed using organic ligands and metal salts, and the lithium sulfide/carbon composite material is reduced in situ.

Benefits of technology

The uniform loading of lithium sulfide and the formation of a hierarchical channel structure are achieved, the conductivity and electrochemical performance of the material are improved, and the cycle stability and energy density of sulfide solid-state batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812448A_ABST
    Figure CN119812448A_ABST
Patent Text Reader

Abstract

The invention provides a lithium sulfide / carbon composite material as well as a preparation method and application thereof. The preparation method comprises the following steps: synthesizing a polystyrene sphere template; soaking the polystyrene sphere template in a mixed solution formed by lithium sulfate, an organic ligand, metal salt and water; and carrying out suction filtration, drying and calcining to obtain the lithium sulfide / carbon composite material. A zeolite imidazate framework structure is formed by using an organic ligand, zinc acetate and lithium sulfate, and lithium sulfide is formed by reducing sulfuric acid in situ by carbon, so that the lithium sulfide is uniformly loaded on a carbon substrate; the graded porous structure formed after the polystyrene spheres are calcined provides a three-dimensional conductive interconnection network and a smooth ion transfer channel for the material, and the conductivity and the electrochemical performance of the material are improved. After the obtained lithium sulfide / carbon composite material is assembled into a battery, the discharge specific capacity of a 0.2 C first circle can reach 836mAh / g, the discharge specific capacity of 50 cycles is 782mAh / g, and the retention rate of the discharge specific capacity of 50 cycles is 93.5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sulfide solid-state batteries, and specifically relates to a sulfide solid-state battery and a lithium sulfide / carbon composite material for an electrolyte thereof, and a preparation method and application thereof. Background Art

[0002] Sulfide solid-state batteries are considered to be an ideal energy source to replace liquid lithium batteries due to their high energy density, high safety, long cycle life and wide operating temperature range. As one of the key materials for sulfide solid-state batteries and their electrolytes, the electrochemical properties of lithium sulfide directly affect the performance of solid-state batteries and their electrolytes. The poor conductivity of lithium sulfide will lead to poor battery cycle stability, and the combination of lithium sulfide and carbon materials can effectively alleviate the above problems.

[0003] At present, there are two main methods for preparing lithium sulfide / carbon composite materials: one is to first synthesize lithium sulfide and a carbon material with controllable morphology, and then further compound the two materials to obtain lithium sulfide / carbon; the other is to directly obtain a carbon / lithium sulfide composite material by high-temperature carbon thermal reduction of lithium sulfate. The first method has a complicated operation process, and it is difficult to evenly compound carbon and lithium sulfide, which will cause uneven dispersion of lithium sulfide in the carbon material and reduce the utilization rate of the active substance lithium sulfide; the second method directly uses lithium sulfate and carbon or carbon-containing organic matter to obtain a carbon / lithium sulfide composite material by high-temperature carbon thermal reduction. Since the particles of lithium sulfate are relatively large, the particles of lithium sulfate cannot be very evenly dispersed in the carbon precursor, and the lithium sulfide particles obtained after carbon thermal reduction will also be relatively large, which will eventually seriously affect the electrochemical properties of the prepared composite material.

[0004] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention

[0005] In view of the problems existing in the prior art, the purpose of the present invention is to provide a lithium sulfide / carbon composite material and its preparation method and application. Among them, lithium sulfide is uniformly loaded on a carbon substrate; a hierarchical porous carbon structure is formed after pyrolysis of a polystyrene sphere template, which not only enhances the conductivity of lithium sulfide, but also provides a three-dimensional conductive interconnection network and a smooth ion transport channel for the active material, thereby improving the electrochemical performance.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a lithium sulfide / carbon composite material, comprising the following steps:

[0008] (1) Synthesis of polystyrene sphere templates;

[0009] (2) immersing the polystyrene sphere template in a mixed solution of lithium sulfate, organic ligand, metal salt and water and allowing to stand;

[0010] (3) leaving the mixture to stand for filtration and drying the solid obtained by filtration;

[0011] (4) After drying, calcining is carried out under a protective gas atmosphere to obtain a lithium sulfide / carbon composite material.

[0012] Preferably, the specific method of step (1) is: mixing the styrene solution with deionized water and passing nitrogen; after passing nitrogen, heating and stirring; then, adding an aqueous solution containing potassium persulfate and continuing to stir; finally, centrifuging and drying to obtain the product.

[0013] Preferably, the nitrogen is introduced for 15 minutes; the heating and stirring temperature is 80-90°C for 30-40 minutes; after adding the aqueous solution containing potassium persulfate, the stirring temperature is 80-90°C for 24-32 hours; the centrifugal speed is 2500-3000 rpm for 24-32 hours.

[0014] Preferably, the volume ratio of the styrene solution to deionized water is (3-4):25; in the aqueous solution containing potassium persulfate, the volume ratio of the mass of potassium persulfate to water is (1-2) g:(20-50) mL; and the volume ratio of the mass of potassium persulfate to the styrene solution is 1 g:(30-40) mL.

[0015] Preferably, in step (2), the organic ligand is benzimidazole, the metal salt is zinc acetate, and the standing time is 12 hours.

[0016] Preferably, in the mixed solution of step (2), the mass ratio of lithium sulfate to water is (1.1-2.3) g:20 mL; the molar ratio of lithium sulfate to benzimidazole is 1:(2-4);

[0017] The mass ratio of zinc acetate to benzimidazole is 1:2-3; the mass ratio of lithium sulfate to the polystyrene sphere template is (1.1-2.3):(2-4).

[0018] Preferably, in step (3), the drying temperature is 60-80° C. and the drying time is 10-24 h.

[0019] Preferably, in step (4), the protective gas is argon or nitrogen; the specific process of the calcination treatment is: reacting at 250-300°C for 3-6 hours; then reacting at 450-500°C for 3-6 hours; then reacting at 725-775°C for 3-6 hours; the lithium sulfide / carbon composite material has a hierarchical pore structure.

[0020] The present invention provides a lithium sulfide / carbon composite material, characterized in that the lithium sulfide / carbon composite material is prepared by the preparation method.

[0021] The present invention provides an application of the lithium sulfide / carbon composite material in preparing a sulfide solid-state battery or a sulfide solid-state electrolyte.

[0022] Beneficial effects:

[0023] The preparation method of the present invention obtains a lithium sulfide / carbon composite material by in-situ reduction in a one-step method, specifically comprising: 1) synthesizing a uniformly arranged polystyrene sphere template; 2) soaking the polystyrene sphere template in a mixed solution of lithium sulfate, a metal salt solution (zinc acetate) and an organic compound ligand (benzimidazole); 3) drying to obtain a precursor; 4) calcining treatment to obtain. Among them, the organic ligand, zinc acetate and lithium sulfate form a zeolite imidazolate framework structure (ZIF), and the carbon in the ZIF ligand in situ reduces sulfuric acid to form lithium sulfide, ensuring that the lithium sulfide is uniformly loaded on the carbon substrate; the hierarchical pore structure formed after the polystyrene sphere is calcined provides the material with a three-dimensional conductive interconnection network and a smooth ion transport channel, thereby improving the conductivity and electrochemical performance of the material. Among them, after the obtained lithium sulfide / carbon composite material is assembled into a battery, the 0.2C first cycle discharge capacity can reach 836mAh / g, the discharge capacity after 50 cycles is 782mAh / g, and the discharge capacity retention rate after 50 cycles is 93.5%. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:

[0025] Figure 1 This is a scanning electron microscope image of the polystyrene sphere template in Example 1 of the present invention.

[0026] Figure 2 This is a scanning electron microscope image of the lithium sulfide / carbon composite material in Example 1 of the present invention.

[0027] Figure 3 This is the XRD diagram of the lithium sulfide / carbon composite material in Example 1 of the present invention. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0029] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0030] In view of the existing problems, the present invention provides a method for preparing a lithium sulfide / carbon composite material, comprising the following steps:

[0031] (1) Synthesis of polystyrene sphere templates;

[0032] (2) immersing the polystyrene sphere template in a mixed solution of lithium sulfate, organic ligand, metal salt and water and allowing to stand;

[0033] (3) leaving the mixture to stand for filtration and drying the solid obtained by filtration;

[0034] (4) After drying, calcining is carried out under a protective gas atmosphere to obtain a lithium sulfide / carbon composite material.

[0035] In a preferred embodiment of the present invention, the specific method of step (1) is: mixing a styrene solution with deionized water and introducing nitrogen; after the nitrogen is introduced, heating and stirring the mixed solution; then, adding an aqueous solution containing potassium persulfate and continuing to stir; finally, centrifuging and drying to obtain the product.

[0036] In a preferred embodiment of the present invention, the volume ratio of the styrene solution to deionized water is (3-4):25; the nitrogen is introduced for 15 minutes; the temperature of the mixed solution is heated and stirred at 80-90°C for 30-40 minutes;

[0037] In a preferred embodiment of the present invention, in the aqueous solution containing potassium persulfate, the mass ratio of potassium persulfate to water is (1-2) g: (20-50) mL; the mass ratio of potassium persulfate to the volume ratio of styrene solution is 1 g: (30-40) mL;

[0038] In a preferred embodiment of the present invention, after adding the aqueous solution containing potassium persulfate, the stirring temperature is 80-90°C for 24-32 hours; the centrifugal speed is 2500-3000 rpm for 24-32 hours;

[0039] In a preferred embodiment of the present invention, in step (2), the organic ligand is benzimidazole; the metal salt is zinc acetate; the mass ratio of zinc acetate to benzimidazole is 1:2-3; the mass ratio of lithium sulfate to polystyrene sphere template is (1.1-2.3):(2-4); the standing time is 12h;

[0040] In a preferred embodiment of the present invention, in the mixed solution of step (2), the mass ratio of lithium sulfate to water is (1.1-2.3) g: 20 mL;

[0041] In a preferred embodiment of the present invention, the molar ratio of lithium sulfate to benzimidazole is 1:(2-4);

[0042] During the standing process, when the organic ligand, zinc acetate and lithium sulfate form a zeolite imidazolate framework (ZIF) material, the lithium sulfate is evenly dispersed in the ZIF material;

[0043] In a preferred embodiment of the present invention, in step (3), the drying temperature is 60-80° C. and the drying time is 10-24 h; after drying, a powdery precursor is obtained;

[0044] In a preferred embodiment of the present invention, the protective gas is argon or nitrogen; the specific process of the calcination treatment is: reacting at 250-300°C for 3-6h; then reacting at 450-500°C for 3-6h; then reacting at 725-775°C for 3-6h;

[0045] In a preferred embodiment of the present invention, in step (4), the lithium sulfide / carbon composite material has a hierarchical pore structure;

[0046] Among them, under calcination conditions, organic ligands and polystyrene balls serve as carbon sources; among them, the organic ligand (benzimidazole) in ZIF can be in situ reduced to lithium sulfate to form lithium sulfide after carbonization, ensuring the uniform distribution of lithium sulfide on the carbon material to form a lithium sulfide / carbon composite material; after the polystyrene balls are calcined, the lithium sulfide / carbon composite material has a hierarchical and orderly pore structure, which provides the material with a three-dimensional conductive network and rich ion shuttle paths, promoting the electrochemical properties of the material.

[0047] The present invention provides a lithium sulfide / carbon composite material, and the lithium sulfide / carbon composite material is prepared by the preparation method.

[0048] The present invention provides an application of a lithium sulfide / carbon composite material in preparing a sulfide solid-state battery.

[0049] The present invention provides application of a lithium sulfide / carbon composite material in preparing a sulfide solid electrolyte.

[0050] The following is a detailed description of a lithium sulfide / carbon composite material and its preparation method and application according to the present invention through specific embodiments.

[0051] Example 1

[0052] This embodiment provides a method for preparing a lithium sulfide / carbon composite material, comprising the following steps:

[0053] (1) Synthesis of polystyrene sphere templates;

[0054] 30 mL of styrene solution was poured into a three-necked flask containing 250 mL of deionized water and nitrogen was introduced. The process lasted for 15 min. The mixed solution was then stirred at 80 ° C for 30 min. Subsequently, 1 g of potassium persulfate (K2S2O8) aqueous solution (25 mL) was added to the mixed solution, the temperature was kept at 80 ° C, and stirring was continued for 24 h to obtain a monodisperse polystyrene sphere colloid. Finally, centrifugation was performed at 2500 rpm for 24 h. After drying, a uniformly arranged polystyrene sphere template was obtained (the scanning electron microscopy of the polystyrene sphere template is as shown in FIG. Figure 1 shown);

[0055] (2) 4.88 g (0.04 mol) of benzimidazole, 2.44 g (0.018 mol) of zinc acetate and 2.27 g (0.02 mol) of lithium sulfate were dissolved in 20 mL of water to form a mixed solution, 2 g of polystyrene sphere template was added, and the solution was allowed to stand for 12 h;

[0056] (3) After standing, the mixture is filtered to ensure that the metal and benzimidazole fully enter the polystyrene sphere template; the solid mixture obtained by filtration is then dried at 70° C. for 10 h to obtain a powdered precursor;

[0057] (4) The precursor is reacted at 250° C. for 6 h, 500° C. for 6 h, and 775° C. for 5 h under a nitrogen atmosphere to obtain a lithium sulfide / carbon composite material.

[0058] The scanning electron microscopy of the obtained lithium sulfide / carbon composite material is as follows Figure 2 As shown by Figure 2 It can be seen that the obtained composite material has a rich pore structure; Figure 3 is the XRD pattern of the obtained lithium sulfide / carbon composite material. Figure 3 It can be seen that the prepared material contains lithium sulfide.

[0059] Example 2

[0060] This embodiment provides a method for preparing a lithium sulfide / carbon composite material, comprising the following steps:

[0061] (1) Synthesis of polystyrene sphere templates;

[0062] 30 mL of styrene solution was poured into a three-necked flask containing 250 mL of deionized water and nitrogen was introduced. The process lasted for 15 min. The mixed solution was then stirred at 80 ° C for 30 min. Subsequently, 1 g of potassium persulfate (K2S2O8) aqueous solution (25 mL) was added to the mixed solution, and the temperature was maintained at 80 ° C and stirred for 24 h to obtain a monodisperse polystyrene sphere colloid. Finally, the mixture was centrifuged at 2500 rpm for 24 h and dried to obtain a uniformly arranged polystyrene sphere template.

[0063] (2) 4.88 g (0.04 mol) of benzimidazole, 2.44 g (0.018 mol) of zinc acetate and 1.51 g (0.014 mol) of lithium sulfate were dissolved in 20 mL of water to form a mixed solution, 2 g of polystyrene sphere template was added, and the solution was allowed to stand for 12 h;

[0064] (3) After standing, the mixture is filtered to ensure that the metal and benzimidazole fully enter the polystyrene sphere template; the solid mixture obtained by filtration is then dried at 70° C. for 10 h to obtain a powdered precursor;

[0065] (4) The precursor is reacted at 250° C. for 6 h, 450° C. for 6 h, and 775° C. for 3 h under a nitrogen atmosphere to obtain a lithium sulfide / carbon composite material.

[0066] Example 3

[0067] This embodiment provides a method for preparing a lithium sulfide / carbon composite material, comprising the following steps:

[0068] (1) Synthesis of polystyrene sphere templates;

[0069] 35 mL of styrene solution was poured into a three-necked flask containing 250 mL of deionized water and nitrogen was introduced. The process lasted for 15 min. The mixed solution was then stirred at 90 ° C for 30 min. Subsequently, 1 g of potassium persulfate (K2S2O8) aqueous solution (25 mL) was added to the mixed solution, and the temperature was maintained at 90 ° C and stirred for 24 h to obtain a monodisperse polystyrene sphere colloid. Finally, the mixture was centrifuged at 3000 rpm for 24 h and dried to obtain a uniformly arranged polystyrene sphere template.

[0070] (2) 4.88 g (0.04 mol) of benzimidazole, 2.44 g (0.018 mol) of zinc acetate and 1.14 g (0.01 mol) of lithium sulfate were dissolved in 20 mL of water to form a mixed solution, 4 g of polystyrene sphere template was added, and the solution was allowed to stand for 12 h;

[0071] (3) After standing, the mixture is filtered to ensure that the metal and benzimidazole fully enter the polystyrene sphere template; the solid mixture obtained by filtration is then dried at 70° C. for 10 h to obtain a powdered precursor;

[0072] (4) The precursor is reacted at 250° C. for 6 h, 450° C. for 6 h, and 775° C. for 3 h under a nitrogen atmosphere to obtain a lithium sulfide / carbon composite material.

[0073] Example 4

[0074] This embodiment provides a method for preparing a lithium sulfide / carbon composite material, comprising the following steps:

[0075] (1) Synthesis of polystyrene sphere templates;

[0076] 35 mL of styrene solution was poured into a three-necked flask containing 250 mL of deionized water and nitrogen was introduced. The process lasted for 15 min. The mixed solution was then stirred at 90°C for 30 min. Subsequently, 1 g of potassium persulfate (K2S2O8) aqueous solution (25 mL) was added to the mixed solution and the temperature was maintained at 90°C and stirred for 24 h to obtain a monodisperse polystyrene sphere colloid. Finally, the mixture was centrifuged at 3000 rpm for 24 h and dried to obtain a uniformly arranged polystyrene sphere template.

[0077] (2) 4.88 g (0.04 mol) of benzimidazole, 2.44 g (0.018 mol) of zinc acetate and 2.27 g (0.01 mol) of lithium sulfate were dissolved in 20 mL of water to form a mixed solution, 4 g of polystyrene sphere template was added, and the solution was allowed to stand for 12 h;

[0078] (3) After standing, the mixture is filtered to ensure that the metal and benzimidazole fully enter the polystyrene sphere template; the solid mixture obtained by filtration is then dried at 70° C. for 10 h to obtain a powdered precursor;

[0079] (4) The precursor is reacted at 250° C. for 3 h, 500° C. for 3 h, and 725° C. for 5 h under a nitrogen atmosphere to obtain a lithium sulfide / carbon composite material.

[0080] Comparative Example 1

[0081] This comparative example provides a method for preparing a lithium sulfide / carbon nanotube composite material. The difference from Example 2 is that this comparative example does not involve the addition of zinc acetate, and the polystyrene sphere template is replaced by carbon nanotubes.

[0082] The preparation method of this comparative example comprises the following steps:

[0083] (1) 4.88 g (0.04 mol) of benzimidazole and 1.51 g (0.014 mol) of lithium sulfate were dissolved in 20 mL of water to form a mixed solution, 2 g of carbon nanotubes were added, and the solution was allowed to stand for 12 h;

[0084] (2) After standing, the mixture was filtered and then dried at 70° C. for 10 h to obtain a powdered precursor;

[0085] (3) The precursor is reacted at 250° C. for 6 h, 450° C. for 6 h, and 775° C. for 3 h under a nitrogen atmosphere to obtain a lithium sulfide / carbon nanotube composite material.

[0086] Comparative Example 2

[0087] This comparative example provides a method for preparing a lithium sulfide / carbon composite material. The difference from Example 2 is that this comparative example does not involve the addition of zinc acetate and polystyrene sphere templates.

[0088] The preparation method of this comparative example comprises the following steps:

[0089] (1) 4.88 g (0.04 mol) of benzimidazole and 1.51 g (0.014 mol) of lithium sulfate were dissolved in 20 mL of water to form a mixed solution, which was allowed to stand for 12 h;

[0090] (2) After standing, the mixture was filtered and then dried at 70° C. for 10 h to obtain a powdered precursor;

[0091] (3) The precursor is reacted at 250° C. for 6 h, 450° C. for 6 h, and 775° C. for 3 h under a nitrogen atmosphere to obtain a lithium sulfide / carbon composite material.

[0092] Comparative Example 3

[0093] This comparative example provides a method for preparing a lithium sulfide / carbon composite material, which is different from Example 2 in that the order of adding lithium sulfide is different.

[0094] The preparation method of this comparative example comprises the following steps:

[0095] (1) Synthesize a polystyrene sphere template according to the method of Example 2;

[0096] (2) 4.88 g (0.04 mol) of benzimidazole and 2.44 g (0.018 mol) of zinc acetate were dissolved in 20 mL of water to form a mixed solution, 2 g of polystyrene sphere template was added, and the solution was allowed to stand for 12 h;

[0097] (3) After standing, the mixture was filtered and then dried at 70° C. for 10 h to obtain a powdered precursor;

[0098] (4) The precursor is reacted at 250° C. for 6 h, 450° C. for 6 h, and 775° C. for 3 h under a nitrogen atmosphere to obtain a carbon material with a multi-level pore structure.

[0099] (5) 1.51 g (0.014 mol) of lithium sulfide and the above carbon material were immersed in 40 ml of ethanol, allowed to stand for 12 h, and dried to obtain a lithium sulfide / carbon composite material.

[0100] Comparative Example 4

[0101] This comparative example provides a method for preparing a lithium sulfide / carbon composite material, which is different from Example 2 in that the amount of lithium sulfide used is different.

[0102] In this comparative example, the 1.51 g (0.014 mol) lithium sulfate added in step (2) of Example 2 was replaced by 0.86 g (0.008 mol) lithium sulfate; the other steps and parameters were the same as those in Example 2.

[0103] Comparative Example 5

[0104] This comparative example provides a method for preparing a lithium sulfide / carbon composite material, which is different from Example 2 in that the amount of the polystyrene sphere template used is different.

[0105] In this comparative example, the 2 g of polystyrene sphere template added in step (2) of Example 2 is replaced by 1 g of polystyrene sphere template; the other steps and parameters are the same as those of Example 2.

[0106] Comparative Example 6

[0107] This comparative example provides a method for preparing a lithium sulfide / carbon composite material, which is different from Example 2 in that the calcination process is different.

[0108] In this comparative example, the reaction at 200°C for 6 h, 400°C for 6 h, and 675°C for 3 h in step (4) of Example 2 is replaced by the reaction at 200°C for 6 h, 400°C for 6 h, and 675°C for 3 h; the other steps and parameters are the same as those in Example 2.

[0109] Application Examples

[0110] Assembly and testing method of button cell: The materials prepared in the above embodiments and comparative examples, conductive carbon black, and PVDF were dispersed in NMP at a mass ratio of 8:1:1, uniformly mixed to form a slurry, coated on aluminum foil, and stamped into a positive electrode sheet with a diameter of 14 mm after drying. A metal lithium sheet was used as the negative electrode, and the electrolyte was 1M LiTFSI / DME:DOL (1:1). The CR2025 button cell was assembled in a glove box filled with argon. The battery was charged and discharged and the cycle stability was tested at a charge and discharge rate of 0.2C in the charge and discharge range of 1.5 to 3.0V.

[0111] Table 1

[0112]

[0113] From the data in Table 1, it can be seen that the materials obtained in Examples 1-4 all have excellent discharge specific capacity and discharge specific capacity retention rate, indicating that the material structure is stable, and after multiple charge and discharge cycles, the active material lithium sulfide can still maintain a high activity.

[0114] Since Comparative Example 1 does not involve the addition of zinc acetate, the organic ligand zinc acetate cannot form a zeolite imidazolate framework (ZIF) with lithium sulfate. Moreover, after the polystyrene sphere template is replaced with carbon nanotubes, a hierarchical pore structure cannot be formed after sintering. Therefore, the cycle capacity and capacity retention rate of the lithium sulfide and carbon nanotube combined material in Comparative Example 1 are lower than those in Example 2. It can be seen that the rich pore structure in the material prepared by the method of the present invention enhances the electrical conductivity of the material and helps to exert the capacity of the lithium sulfide active substance.

[0115] Since Comparative Example 2 does not involve the addition of zinc acetate and polystyrene sphere templates, the material obtained in Comparative Example 2 does not have a hierarchical pore structure, that is, the cycle capacity and capacity retention rate of the material obtained in Comparative Example 2 are much lower than those in Example 2, indicating that the multi-level pore structure is conducive to the exposure of active substances, enhances the activity of the material, and helps to exert its capacity.

[0116] The cycle capacity and capacity retention rate of the material obtained in Comparative Example 3 are lower than those in Example 2. This is because Example 2 is a composite material obtained by an in-situ carbon thermal reduction reaction, and the active substance lithium sulfide has good bonding with the material. The material obtained in Comparative Example 3 is a secondary composite of lithium sulfide and a porous carbon material, and the direct bonding between the two materials is weak, resulting in the loss of active substances during the charge and discharge process, so the cycle capacity and capacity retention rate are low.

[0117] The cycle capacity of the material obtained in Comparative Example 4 is lower than that in Example 2. This is because the amount of lithium sulfate used in Comparative Example 4 is low, and the active material generated during the reaction is lower than that in Example 2, so the cycle capacity is low.

[0118] The cycle capacity and capacity retention rate of the material obtained in Comparative Example 5 are lower than those in Example 2. This is because the amount of polystyrene balls used in Comparative Example 5 is low, and the pore structure richness of the carbon material generated during the reaction is lower than that in Example 2, so the cycle capacity and capacity retention rate are low.

[0119] The cycle capacity and capacity retention rate of the material obtained in Comparative Example 6 are lower than those in Example 2. This is because during the sintering process of the material, the reaction temperature is low and the carbon thermal reaction is incomplete, resulting in low active material content and low degree of graphitization. As a result, the material structure is the same, but the conductivity is lower than that in Example 2, so the cycle capacity is low.

[0120] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a lithium sulfide / carbon composite material, characterized in that: The steps include: (1) Synthesis of polystyrene sphere templates; (2) immersing the polystyrene sphere template in a mixed solution of lithium sulfate, organic ligand, metal salt and water and allowing to stand; (3) leaving the mixture to stand for filtration and drying the solid obtained by filtration; (4) After drying, calcining is carried out under a protective gas atmosphere to obtain a lithium sulfide / carbon composite material.

2. The preparation method according to claim 1, characterized in that The specific method of step (1) is: mixing the styrene solution with deionized water and introducing nitrogen; after the nitrogen introduction is completed, heating and stirring; then, adding an aqueous solution containing potassium persulfate and continuing to stir; finally, centrifuging and drying to obtain the product.

3. The preparation method according to claim 2, characterized in that: The nitrogen is introduced for 15 minutes; the heating and stirring temperature is 80-90°C for 30-40 minutes; after adding the aqueous solution containing potassium persulfate, the stirring temperature is 80-90°C for 24-32 hours; the centrifugal speed is 2500-3000 rpm for 24-32 hours.

4. The preparation method according to claim 2, characterized in that: The volume ratio of styrene solution to deionized water is (3-4):25; in the aqueous solution containing potassium persulfate, the volume ratio of potassium persulfate to water is (1-2) g:(20-50) mL; the volume ratio of potassium persulfate to styrene solution is 1 g:(30-40) mL.

5. The preparation method according to claim 1, characterized in that: In step (2), the organic ligand is benzimidazole, the metal salt is zinc acetate, and the standing time is 12 hours.

6. The preparation method according to claim 5, characterized in that: In the mixed solution of step (2), the mass ratio of lithium sulfate to water is (1.1-2.3) g:20 mL; the molar ratio of lithium sulfate to benzimidazole is 1:(2-4); The mass ratio of zinc acetate to benzimidazole is 1:2-3; the mass ratio of lithium sulfate to the polystyrene sphere template is (1.1-2.3):(2-4).

7. The preparation method according to claim 1, characterized in that: In step (3), the drying temperature is 60-80°C and the drying time is 10-24h.

8. The preparation method according to claim 1, characterized in that: In step (4), the protective gas is argon or nitrogen; the specific process of the calcination treatment is: reacting at 250-300°C for 3-6 hours; then reacting at 450-500°C for 3-6 hours; then reacting at 725-775°C for 3-6 hours; the lithium sulfide / carbon composite material has a hierarchical pore structure.

9. A lithium sulfide / carbon composite material, characterized in that: The lithium sulfide / carbon composite material is prepared by the preparation method described in any one of claims 1-8.

10. Use of the lithium sulfide / carbon composite material according to claim 9 in the preparation of a sulfide solid-state battery or a sulfide solid-state electrolyte.